2018
DOI: 10.1007/s12526-018-0889-2
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and distribution of Arctic Echinoderes species (Kinorhyncha: Cyclorhagida), with the description of one new species and a redescription of E. arlis Higgins, 1966

Abstract: The kinorhynch fauna from Svalbard and the Arctic Ocean north of Svalbard was explored, and a total of nine species of Echinoderes was identified. Two species were new to science, and one, Echinoderes balerioni sp. nov., is described. Echinoderes balerioni sp. nov. is characterized by the presence of short middorsal spines on segments 4, 6, and 8, and in lateroventral positions on segments 6 to 9. Tubes are present in laterodorsal, sublateral, and ventrolateral positions on segment 2, lateroventral positions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 28 publications
0
16
1
Order By: Relevance
“…Species with a geographically wide distribution are e.g., Ce. barbanigra found in the Gulf of Mexico, the Caribbean Sea, Bermuda, and the Dominican Republic at a depth ranging from 2 m to 57.5 m, E. ohtsukai found on both the eastern and western coasts of the Pacific Ocean in the intertidal zone, and E. tchefouensis found in the East China Sea, South China Sea, Celebes Sea, Singapore Strait, and Mariana Islands at a depth ranging from 0 m to 140 m (Sørensen et al 2012b, 2016; Yamasaki and Kajihara 2012; Neuhaus et al 2014; Herranz and Leander 2016). Species from a bathymetrically wide range are e.g., Echinoderes arlis Higgins, 1966, Echinoderes drogoni Grzelak & Sørensen, 2018, Echinoderes eximus Higgins & Kristensen, 1988, Echinoderes peterseni Higgins & Kristensen, 1988, and Echinoderes rhaegali Grzelak & Sørensen, 2018, all found in the Arctic Ocean, at depths ranging from 236 m to 940 m ( E. arlis ), 78 m to 2,200 m ( E. drogoni ), 60 m to 940 m ( E. eximus ), 24 m to 940 m ( E. peterseni ), and 78 m to 940 m ( E. rhaegali ) (Grzelak and Sørensen 2018b). However, their distribution records are not both geographically and bathymetrically wide like those of E. pterus sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Species with a geographically wide distribution are e.g., Ce. barbanigra found in the Gulf of Mexico, the Caribbean Sea, Bermuda, and the Dominican Republic at a depth ranging from 2 m to 57.5 m, E. ohtsukai found on both the eastern and western coasts of the Pacific Ocean in the intertidal zone, and E. tchefouensis found in the East China Sea, South China Sea, Celebes Sea, Singapore Strait, and Mariana Islands at a depth ranging from 0 m to 140 m (Sørensen et al 2012b, 2016; Yamasaki and Kajihara 2012; Neuhaus et al 2014; Herranz and Leander 2016). Species from a bathymetrically wide range are e.g., Echinoderes arlis Higgins, 1966, Echinoderes drogoni Grzelak & Sørensen, 2018, Echinoderes eximus Higgins & Kristensen, 1988, Echinoderes peterseni Higgins & Kristensen, 1988, and Echinoderes rhaegali Grzelak & Sørensen, 2018, all found in the Arctic Ocean, at depths ranging from 236 m to 940 m ( E. arlis ), 78 m to 2,200 m ( E. drogoni ), 60 m to 940 m ( E. eximus ), 24 m to 940 m ( E. peterseni ), and 78 m to 940 m ( E. rhaegali ) (Grzelak and Sørensen 2018b). However, their distribution records are not both geographically and bathymetrically wide like those of E. pterus sp.…”
Section: Discussionmentioning
confidence: 99%
“…To date, more than 260 kinorhynchs species are known from around the world (Grzelak and Sørensen 2018a, b; Yamasaki et al 2018). Many ecological studies on meiofauna from various regions and environments often report the presence of Kinorhyncha, but unfortunately provide only phylum-level identification (e.g., Grzelak and Kotwicki 2012; Nomaki et al 2016; Riera et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…16 ). This shows that Pycnophyidae is just as diverse in the Arctic as Echinoderidae, which currently is represented with 13 species in the Arctic ( Grzelak & Sørensen, in press ). Interestingly, Pycnophyidae and Echinoderidae are so far the only two kinorhynch families that have been recorded from the Arctic Region.…”
Section: Discussionmentioning
confidence: 98%
“… Grzelak & Sørensen (in press) suggested that at least some species of Arctic Echinoderes appeared to show a circumpolar distribution. A similar distribution pattern is not really clear for any of the recorded pycnophyids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation